Are chronic neck pain, scapular dyskinesis and altered scapulothoracic muscle activity interrelated?: A case-control study with surface and fine-wire EMG. (December 2016) - Castelein, Birgit; Cools, Ann; Parlevliet, Thierry; Cagnie, Barbara
Abstract: Objectives: The function of the scapula is important in normal neck function and might be disturbed in patients with neck pain. The surrounding muscular system is important for the function of the scapula. To date, it is not clear if patients with idiopathic neck pain show altered activity of these scapulothoracic muscles. Therefore, the objective of this study was to investigate differences in deeper and superficial lying scapulothoracic muscle activity between patients with idiopathic neck pain and healthy controls during arm elevation, and to identify the influence of scapular dyskinesis on muscle activity. Methods: Scapular dyskinesis was rated with the yes/no method. The deeper lying (Levator Scapulae, Pectoralis Minor (Pm) and Rhomboid major) and superficial lying (Trapezius and Serratus Anterior) scapulothoracic muscles' activity was investigated with fine-wire and surface EMG, respectively, in 19 female subjects with idiopathic neck pain (age 28.3 ± 10.1 years, average duration of neck pain 45.6 ± 36.3 months) and 19 female healthy control subjects (age 29.3 ± 11.7 years) while performing scaption and towel wall slide. Possible interactions or differences between subject groups, scapular dyskinesis groups or phases of the task were studied with a linear mixed model. Results: Higher Pm activity during the towel wallslide (p = 0.024, mean difference 8.8 ± 3.3% MVIC) was shown in patients with idiopathic neck pain in comparison with healthy controls. For the MT, a significant group ∗ dyskinesis interaction effect was found during scaption which revealed that patients with neck pain and scapular dyskinesis showed lower Middle Trapezius (MT) activity in comparison with healthy controls with scapular dyskinesis (p = 0.029, mean difference 5.1 ± 2.2% MVIC). Conclusions: In the presence of idiopathic neck pain, higher Pm activity during the towel wallslide was found. Patients with neck pain and scapular dyskinesis showed lower MT activity in comparison with healthy controls with scapular dyskinesis during scaption. Scapular dyskinesis did not have a significant influence on scapulothoracic muscle activity.